2021
DOI: 10.3390/ijms22147364
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine May Oppose Other Neuromodulators to Impact Alzheimer’s Disease

Abstract: While much of biomedical research since the middle of the twentieth century has focused on molecular pathways inside the cell, there is increasing evidence that extracellular signaling pathways are also critically important in health and disease. The neuromodulators norepinephrine (NE), serotonin (5-hydroxytryptamine, 5HT), dopamine (DA), acetylcholine (ACH), and melatonin (MT) are extracellular signaling molecules that are distributed throughout the brain and modulate many disease processes. The effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Finally, overactivation of the SNS has been implicated in the development of AD. NE is thought to be functionally largely opposed to the neuromodulators serotonin, dopamine, acetylcholine and melatonin, which are distributed throughout the brain and modulate many processes in the pathophysiology underlying AD ( Fitzgerald, 2021 ). ( Limitation: see discussion ).…”
Section: Non-communicable Diseases Caused By Smoking: Dysregulation O...mentioning
confidence: 99%
“…Finally, overactivation of the SNS has been implicated in the development of AD. NE is thought to be functionally largely opposed to the neuromodulators serotonin, dopamine, acetylcholine and melatonin, which are distributed throughout the brain and modulate many processes in the pathophysiology underlying AD ( Fitzgerald, 2021 ). ( Limitation: see discussion ).…”
Section: Non-communicable Diseases Caused By Smoking: Dysregulation O...mentioning
confidence: 99%
“…Interestingly, patients exposed to beta-blockers appear to have a lower incidence of dementia [31], while their role in Parkinson's disease is more controversial [32]. It has been recently suggested that the development of amyloid plaques and locus coeruleus degeneration are compensatory processes in response to long-term elevated noradrenergic signalling [33].…”
Section: The Question Of Locus Coeruleus Overactivitymentioning
confidence: 99%